A day full of math games & activities. Find one near you.
A day full of math games & activities. Find one near you.
A day full of math games & activities. Find one near you.
A day full of math games & activities. Find one near you.
Given the function f(x) = 3(x + 2) - 4, solve for the inverse function when x = 2.
Solution:
Given: Function f(x) = 3(x + 2) - 4
Consider f(x) as y
y = 3(x + 2) - 4
Replace x by y
x = 3(y + 2) - 4
It can be written as
x + 4 = 3(y + 2)
Divide both sides by 3
(x + 4)/3 = y + 2
(x + 4)/3 - 2 = y
So f-1(x) = (x + 4)/3 - 2
Let us solve by substituting x as 2
f-1(2) = (2 + 4)/3 - 2
By further calculation
f-1(2) = 6/3 - 2
f-1(2) = 2 - 2
f-1(2) = 0
Therefore, the inverse function when x = 2 is 0.
Given the function f(x) = 3(x + 2) - 4, solve for the inverse function when x = 2.
Summary:
Given the function f(x) = 3(x + 2) - 4, the inverse function when x = 2 is 0.
Math worksheets and
visual curriculum
visual curriculum